Isolation and Identification of the Chitinolytic Bacteria from Rumen Ecosystem - Rahayu, Sri; Suhartati, FM; Rimbawanto, EA; Iriyanti, Ning (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2003)
Rumen is an interesting ecosystem for microbial exploration and their products. Isolation of the chitinolytic bacteria from the rumen ecosystem found 109 colonies that produced clear zone, 84 colonies (86%) anaerobic and 17 colonies (14%) aerobic. Clear zone appeared in the third and fourth days incubation. Four potential isolates were chosen for identification purposes. Results showed that the bacteria were sticky, gram-positive, motile, endospore-forming, mesophilic and aerobic. It was supposed to Bacillus spp. the optimal pH and temperature to produce chitinase from isolate 18 are pH 6.0 and temperature of 35-40ÂºC. Divalent cations Mg, Ca, Zn, and Mn increase chitinase activity, while Cu and Co inhibit enzyme activity. When isolate 18 was grown on shrimp waste meal, it showed aptimal activity on the fifth days incubation. (Animal Production 5(2): 73-78 (2003)Â Key Words : Isolation, Identification, Chitinolytic Bacteria, Rumen